A study into the effect of total quality management practices on customer satisfaction by a consortium - a case study of ABP Consult - Pela, Arku (2017)
A Thesis submitted to the Department of Building Technology, College of Art and Built Environment in partial fulfillment of the requirements for the degree of Master of Science,